Pengembangan Alat Ukur Kecepatan Reaksi Tendangan Dan Pukulan Berbasis Whole Body Reaction (WBR) Pada Atlet Pencak Silat - Achmad Zayul Mustain; Ressa Akbar (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2021)
Speed ​​is very necessary and can affect a person's appearance both when attacking and defending. Velocity is classified into two types, namely roasting speed and reaction speed. Reaction speed is the ability for individuals to respond to stimuli optically (eye), tactile (skin) and acoustically (ears). The output of reaction speed can be measured as reaction time. The aim of this research is to develop a measuring instrument for kicks and punches reaction speed based on a whole body reaction (WBR) speed measuring instrument. The design of this study uses the ADDIE learning media development model which stands for Analysis, Design, Development and Implementation (development and implementation) and Evaluation. Testing the feasibility of measuring the reaction speed of kicks and punches is assisted by material experts, media experts and physicists. The research subjects consisted of small groups and large groups. Small group and large group respondents try to measure reaction speed by making kicks and punches. After that they were given a questionnaire to fill out and assess the appropriateness of the tool and its design. From the results of this study, it was found that the small group got a total score of 83.4% so that the category was quite feasible. The results of the questionnaire from the large group showed that a total score of 82.8% was categorized as quite feasible